2019
DOI: 10.1021/acsami.9b03526
|View full text |Cite
|
Sign up to set email alerts
|

New Generation of Mesoporous Silica Membranes Prepared by a Stöber-Solution Pore-Growth Approach

Abstract: Membranes consisting of uniform and vertically organized mesopores are promising systems for molecular filtration because of the possibility to combine high-flux and high-rejection properties. In this work, a new generation of mesoporous silica membranes (MSMs) have been developed, in which an organized mesoporous layer is directly formed on top of a porous ceramic support via a Stöber-solution pore-growth approach. Relevant characterization methods have been used to demonstrate the growth of the membrane sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This approach allows modulation of the polymer nanostructures for specific applications but is not suitable for practical separation applications in industry due to the limited surface area of the AAO supports when dealing with cubic meters of water and their fragility when exposed to harsh conditions. 19 In contrast to previous studies done on AAO supports or mesoporous organosilica layers, we looked at defined and rigid mesoporous ceramic membranes with relatively low tortuosity. Alumina (γor α-phase) membranes are commercially predominant in the market and are available in the shape of discs and tubes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach allows modulation of the polymer nanostructures for specific applications but is not suitable for practical separation applications in industry due to the limited surface area of the AAO supports when dealing with cubic meters of water and their fragility when exposed to harsh conditions. 19 In contrast to previous studies done on AAO supports or mesoporous organosilica layers, we looked at defined and rigid mesoporous ceramic membranes with relatively low tortuosity. Alumina (γor α-phase) membranes are commercially predominant in the market and are available in the shape of discs and tubes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…When a polymer is confined within a micrometer-thick rigid AAO template comprising of vertically oriented large pores (10–100 nm) that are not tortuous, the crystallization behavior experiences dramatic changes as the pore size is reduced. This approach allows modulation of the polymer nanostructures for specific applications but is not suitable for practical separation applications in industry due to the limited surface area of the AAO supports when dealing with cubic meters of water and their fragility when exposed to harsh conditions . In contrast to previous studies done on AAO supports or mesoporous organosilica layers, we looked at defined and rigid mesoporous ceramic membranes with relatively low tortuosity.…”
Section: Introductionmentioning
confidence: 99%
“…This parallel structure was originally reported in hexagonal close-packed (HCP) CTAB-templated mesoporous films by Lu et al Tolbert et al developed a method to orient the mesostructure in CTAB-templated silica by applying a magnetic field, but a very high field strength (12 T) is needed, which would limit opportunities for scaling production of films aligned by this approach. , Robertson et al also obtained vertically aligned pores in CTAB-templated silica films through electrochemically assisted surfactant assembly but this approach is restricted to conductive substrates . Pizzoccaro-Zilamy et al recently reported solution-phase synthesis of vertically oriented silica membranes on porous supports, but this approach is not as scalable as EISA. Chemical modification of surfaces such that they interact equally with the head and tail of the surfactant template, possibly combined with confinement between two modified surfaces, has been shown to be a reproducible approach to synthesize Pluronic P123-templated silica films with orthogonally oriented HCP (o-HCP) pores by EISA on different substrates including membrane supports. While effective, this strategy has only been demonstrated with block copolymer templates, which typically give pore diameters in excess of 5 nm .…”
Section: Introductionmentioning
confidence: 85%
“…9, 18 Robertson et al also obtained vertically aligned pores in CTAB-templated silica films through electrochemically assisted surfactant assembly but this approach is restricted to conductive substrates. 19 Pizzoccaro-Zilamy et al recently reported solution-phase synthesis of vertically oriented silica membranes on porous supports, 20 but this approach is not as scalable as EISA. Chemical modification of surfaces such that they interact equally with the head and tail of the surfactant template, possibly combined with confinement between two modified surfaces, has been shown to be a reproducible approach to synthesize Pluronic P123-templated silica films with orthogonally oriented HCP (o-HCP) pores by EISA on different substrates including membrane supports.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared membranes delivered a quite stable performance over 2 years for pervaporation dehydration of 95 wt% n-butanol. Afterwards, the applications of BTESE membranes have expanded to gas separation, RO and nanofiltration (NF) processes [20][21][22]. The only weakness of BTESE membranes was the relatively low water permeance, mainly due to the confined pore size and the hydrophobic nature of the networks, which would not allow water to rapidly transport through the membrane.…”
Section: Introductionmentioning
confidence: 99%